Problematika Regulasi Ojek Online Dalam Masa Pembatasan Sosial Berskala Besar Covid-19 - Azizah Ratu Buana (UIN Syarif Hidayatullah Jakarta, 2020)
AbstractOnline Transportation application has become one of application platform that is very influential for Indonesian people. Application users; both as passengers, drivers, and cooperation partners, were greatly affected by the emergence of the COVID-19 virus outbreak. The government as a policy holder began to bring up various regulations as a form of COVID-19 prevention. PSBB (Large-scale Social Limitation) rules in several regions have been enacted and regulations related to online transportation are also issued by the government. However, in implementing regulations there are overlapping rules between institutions such as the Minister of Transportation's Regulation which was found to be in conflict with the Minister of Health's Regulation.Keyword: Covid-19, PSBB, Ojek Online AbstrakAplikasi Ojek Online telah menjadi salah satu aplikasi yang sangat berpengaruh bagi masyarakat Indonesia. Pengguna aplikasi baik sebagai penumpang, driver, maupun mitra kerjasama terkena dampak yang besar dengan munculnya wabah virus COVID-19. Pemerintah sebagai pemegang kebijakan mulai memunculkan berbagai regulasi sebagai bentuk pencegahan COVID-19. Aturan PSBB (Pembatasan Sosial Berskala Besar) dalam beberapa daerah telah diberlakukan dan regulasi terkait transportasi ojek online juga diterbitkan oleh pemerintah. Namun, dalam pemberlakuan regulasi terdapat aturan yang saling tumpang tindih antar lembaga seperti Peraturan Menteri Perhubungan yang ditemukan bertentangan dengan Peraturan Menteri Kesehatan.Kata Kunci: Covid-19, PSBB, Ojek Online